The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)
fs-ref-orig: Bouchard, L., Colman, I., Dubois, A., & Sucha, E. (2019). The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012. University of Ottawa & Institut du Savoir Montfort. fs-code-orig: Bouchard-2019e

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)
Nombre de pages: 94 fs-ref-orig: Bouchard, L., Colman, I., Dubois, A. et Sucha, E. (2019). La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012. Université d’Ottawa et Institut du Savoir Montfort. fs-code-orig: Bouchard-2019a

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d’Ottawa et Institut du Savoir Montfort, 2019)
Nombre de pages: 24

The health impact of living in a nursing home with a predominantly different spoken language: Lettor to the Editor - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes. Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services. French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones. However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored. We conducted a population-based retrospective cohort study to assess the impact of language discordance on hospitalizations, emergency department (ED) visits, and mortality in a cohort of 122,416 incident admissions to nursing homes in Ontario between 2010 and 2016.